2016
DOI: 10.1111/imj.13085
|View full text |Cite
|
Sign up to set email alerts
|

Quality of warfarin control in atrial fibrillation patients in South East Queensland, Australia

Abstract: The observed mean TTR of over 80% is superior to the minimum recommended threshold of 60%. The TTR achieved by the Queensland pathology practice demonstrates that dedicated warfarin programmes can produce high-quality warfarin care, ensuring the full benefit of warfarin for Australian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
2
12
1
1
Order By: Relevance
“…However, a previous study of the same warfarin program found a mean TTR of 81% with less than 3% of patients with a TTR<60% [13] suggesting slightly lower control in patients changed to NOAC. Interestingly Pokorney and Granger [14] found data does not support a substantially larger benefit of NOACs in patients with poor warfarin control but found a modest absolute benefit from NOACs in patients naïve to oral anticoagulants.…”
Section: Discussionmentioning
confidence: 81%
“…However, a previous study of the same warfarin program found a mean TTR of 81% with less than 3% of patients with a TTR<60% [13] suggesting slightly lower control in patients changed to NOAC. Interestingly Pokorney and Granger [14] found data does not support a substantially larger benefit of NOACs in patients with poor warfarin control but found a modest absolute benefit from NOACs in patients naïve to oral anticoagulants.…”
Section: Discussionmentioning
confidence: 81%
“…Further to this, studies from countries with a high quality of warfarin control in general practice have demonstrated no significant change in TTR with dedicated warfarin clinics. Warfarin control in Australia has been reported to be relatively high, with TTRs of 73%‐76% in clinical trial settings and TTRs of 55%to 81% in real‐world practice settings. However, to date, there are no Australian data comparing warfarin management by the GP and dedicated anticoagulant clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Bereznicki et al reported an overall TTR of 64.0% in Australian veterans taking warfarin. Further Australian studies have reported regionally specific TTRs of 69.1% in southern Tasmanian patients, 55.4% in the top end of the Northern Territory, and 79%‐81% in Queensland . Australian approaches for managing patients taking warfarin include care by the GP or by laboratory care programmes .…”
Section: Introductionmentioning
confidence: 99%
“…Nos estudos, o valor do TTR variou de 49,5% a 81% (CELIK et al, 2015;BERNAITIS et al, 2016), e pacientes com hipertensão, doença da artéria coronária, insuficiência cardíaca congestiva ou hábito de fumar apresentaram níveis de TTR significativamente mais baixos do que os demais (CELIK et al, 2015). Assim, o TTR nos pacientes tratados com varfarina foi inversamente associado com a ocorrência de eventos tromboembólicos sistêmicos e de mortalidade (PROIETTI et al, 2016).…”
Section: ____________________________________________________________unclassified